TRIZ AND HDC SAPPHIRE GROWTH PROCESS - Medvecký, Štefan; Mikita, Miroslav; Hoc, Michal; Kajan, Juraj (Journal of Applied Engineering Science, 2017)
The application of Theory of Inventive Problem Solving (TRIZ) into sapphire single crystal growth process provided thorough analysis of a problem as well as introduced two conceptually new solutions. The innovation of the Bagdasarov – Horizontally Directed Crystallization (HDC) by resolving the pollution of the observation window improves the control over the process. The increased accuracy of the control leads to supreme quality of the resultant sapphire single crystal. The ultimate goal of betterment is the complete automation of the growth process.
Keywords: Innovation; Automation; HDC Bagdasarov method; Sapphire single crystal; TRIZ